THE ROLE OF TEACHERS AS MANAGERS IN IMPROVING ACADEMIC ACHIEVEMENT AT MADRASAH IBTIDAIYAH DARUL HIKMAH AL FATIMIYAH BESUKI SITUBONDO - Haqiqi, Mohammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research examines the role of teachers as manager in improving academic achievement at Madrasah Ibtidaiyah Darul Hikmah Al Fatimiyah Besuki Situbondo. The main focus of the research is to identify managerial strategies implemented by teachers in an effort to improve student academic achievement. The research method used was qualitative with a case study approach, involving in-depth interviews and observations of teachers, students and madrasah heads. The research results show that teachers at Madrasah Ibtidaiyah Darul Hikmah Al Fatimiyah play a crucial role as manager in managing the learning process. They are not only responsible for delivering lesson material, but also have a strategic role in planning, organizing, implementing and supervising learning. Teachers as manager are recognized as having a role in designing innovative learning programs, motivating students, and creating a conducive learning environment. Apart from that, teachers also act as facilitators in building good relationships between madrasah, students and parents. Parental involvement in supporting learning at home is recognized as an important factor that supports better academic achievement. In this context, the teacher's role as manager also includes coordinating with parents to maximize their support for their children's learning. This research presents an in-depth understanding of the managerial role of teachers and their contribution to increasing academic achievement at Madrasah Ibtidaiyah Darul Hikmah Al Fatimiyah. The implications of these findings can help develop more effective managerial strategies in improving the quality of education in similar institutions.